Profile of Medicolegal Autopsy Cases Conducted at Tertiary Care Centre, Kalaburagi, Karnataka - Manish K1 , KhajaAzizuddin Junaidi2 , Deepak S3 , Umesh SR4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: The profile of medico legal autopsy cases is important in order to know the death statistics in a region due to unnatural causes. The main objectives of the study were: a) To ascertain the various aspects of unnatural deaths, b) To analyze the probable reasons for the same & c) To find remedial measures to bring down the incidence. Materials and Method: The present study is a retrospective study of autopsies performed at GIMS, District Hospital, Kalaburagi, Karnataka from January 2018 to December 2018. During this period a total of 647 autopsy cases were conducted. Relevant information and subjective data like age, sex, marital status & manner of death have been collected from medicolegal autopsy register from January 2018 to December Results: Out of 647 cases analyzed, maximum number of autopsies were in the age group of 21-30 years with 204 cases(31.5%). Majority of victims were males 437(67.5%). Hindus were majority in number with 540 cases(83.4%), married were 432(66.8%) & unmarried were 215 cases(33.2%). In our study 73% were rural residents & only 27% were urban. Accident, Suicide and Homicide deaths were 282(43.6%), 331(51.2%)& 34(5.2%) cases respectively. Natural deaths were seen in 14% cases. Maximum number of deaths were due to road traffic accidents with 212 cases (32.8%) followed by poisoning with 85 cases (13.1%). Out of total 647 cases maximum number of autopsy cases 317(49.1%) were conducted in the month of May to August. Conclusion: In our present study it is observed that maximum cases were in 3rd decade of life, Males outnumbered females, rural residents were more in number. Hindus being majority formed bulk of cases. RTA, Poisoning & burns were seen as leading cause of death & maximum deaths were in the month of May to August.